The impact of small and medium enterprise financing on the profit ability of conventional and Islamic banks in Malaysia - Ahmad Tarmizi, Abu Hanipah (2019)
Small and Medium Enterprises (SMEs) play a very significant role in the economy in terms of balanced and sustainable growth, employment generation, development of entrepreneurial skills and contribution to export earnings. However, despite their importance to the economy, most SMEs are not able to stand up to the challenges of globalization, mainly because of difficulties in securing financing for their development. The difficulties faced by SMEs in assessing financial support are said to be contributed to their high risk profiles. SMEs are regarded as risky enterprises by the financial institution for a number of reasons. On that score, this study sets out to assess the trend as well as the impact of SME financing, along with other independent variables, on the profitability of 12 Conventional and 12 Islamic banks in Malaysia from the period of 2004 to 2017. Two dependent variables, Return on Asset (ROA) and Net Interest Margin (NIM) are selected as proxies for bank profitability. All the variables are then regressed using panel data of Random Effects (RE) and Fixed Effects (FE) models with robust standard errors. The regression result shows that while SME financing have a significant but negative impact on Conventional banks' profitability, it has an insignificant and negative impact on Islamic banks' profitability.